Simbol Religiusitas Tari Topeng Panji Cirebon - Toto Amsar Suanda (EKSPRESI, 2009)
Religiosity Symbol in The Cirebon Topeng Panji Dance. This research aimed at understanding religiosity in the Cirebon Topeng Panji Dance. The data were collected through observation and intense interview with the mask puppet puppeteers and mask dancers. The puppeteers called topeng dance as alive but dead, dead but alive. The symbol contained  in Topeng Panji Dance was a dialogue discussing human and humanity problems in general. When human being fused himself imaginatively in a broader scope and he enjoyed it, he would be the part of the life he performed. Topeng Panji Dance could be seen as an emblem of moral truth not as a subordinate and a servant for sensual enjoyment. It was not only valuable in itself but also a value outside it that could be tracked down from various points of view. Keywords: Topeng Panji, simbol, religiusity.